Promoting Open Education through Gamification in Higher Education: The OpenGame project - García-Holgado, Alicia; García-Peñalvo, Francisco; de la Higuera, Colin; Teixeira, Antonio; Ehlers, Ulf-Daniel; Brunton, James; Nascimbeni, Fabio; Padilla-Zea, Natalia; Burgos, Daniel (ACM International Conference Proceeding Series, 2021)
Open education enables the transformation of higher education institutions to increase access to and quality of education, which is directly connected with the fourth sustainable development goal defined by UNESCO. Despite the need for this transformation, higher education institutions face a barrier. Educators are resistant to embracing the use of OERs and OEPs. The OpenGame project aims to contribute to the uptake of open educational resources and open educational practices among educators in higher education in an innovative and motivating way through the development of a gamified and situated learning experience in open education. This work introduces the main characteristics of the project and describes the main results achieved during the first months of the project. © 2020 Owner/Author.
Keywords: gamification; higher education; open education; open framework; open practices; teacher training; Scopus(2)